Forest Owners' Organizations in North and Central Portugal - assessment of success - Feliciano, Diana (2014)
Background and purpose: The emergence of forest owners’ organizations (FOOs) in Portugal occurred in the 1990s. Fifteen years later there were 173 FOOs providing services to the private forest owners and also to the whole of society. This study aims to evaluate the success of FOOs in increasing their membership and the quantity of services provided. Material and methods: Eight FOOs from the North and Central Portugal were chosen as case studies. Quantitative data on membership numbers and number of services provided by the eight case studies were collected from the archives of FORESTIS or directly at the FOOs headquarters. Qualitative data from newsletters, annual reports, local newspapers and letters were also collected to be further analysed. Secondary data collected cover a period of substitute 10 years by 11 years (1994-2005). In addition, eight interviews to members of staff or FOOs directors were conducted in 2005. It was hypothesised that the number of members and the quantity of services provided may be interrelated and that the turnover of staff and their productivity influence the success of FOOs in increasing their membership and providing technical advice services. Results and conclusion: The study showed that although most FOOs were successful in making their membership grow, there were big differences in the number of members, in the forest area covered by them and in the quantity of services provided. It was concluded that human capital, financial capital and path dependence were the factors that most constrained the success FOOs in North and Central Portugal.